Portable Pico Linear Generator Design with Different Magnet Shapes for Wave Energy Conversion System - Nursyamimi Shahabudin; Taib Ibrahim; Naily Akmal Mohd Zamri (Institute of Advanced Engineering and Science, 2017)
There are abundant of wave energy converter technologies available to convert wave energy into useable energy. However, most of them are huge and suitable for large application. Thus, this paper aimed to propose portable pico generator designs for small scale application. Investigation on the performance of designs with varying halbach magnet shapes was mainly focused and discussed. Two designs of different magnet shape i.e. triangular and trapezoid were proposed. Open-circuit simulation and optimization results were obtained using Finite Element Method. From the results, it was found out that Trapezoid Magnet Design produced better performance and lower material cost compared to another proposed design, Triangular Magnet as well as conventional Rectangular Magnet shape.